The Indochinese Refugee Movement and the Subsequent Evolution of UNHCR and Canadian Resettlement Selection Policies and Practices - Casasola, Michael (Refuge: Canada's Journal on Refugees, 2016)
The Indochinese refugee movement cast a long shadow over subsequent resettlement operations. UNHCR has since asserted greater leadership, with resettlement becoming more individually focused and globally diverse, but also more complex. Canadian policy has also evolved to become increasingly focused on protection and supportive of UNHCR’s durable solution activities. This article seeks to compare UNHCR and Canadian resettlement selection policy and practice in place during the time of the Indochinese movement up to mid-2015. It highlights key elements in the evolution of UNHCR and Canadian resettlement policy and the factors behind them. It also identifies aspects of the Indochinese movement that are relevant to contemporary refugee policy.